2004
DOI: 10.1590/s0100-879x2004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat saturation on lipid metabolism, arachidonic acid turnover and peritoneal macrophage oxidative stress in mice

Abstract: We investigated the effects of a saturated fat diet on lipid metabolism and arachidonic acid (AA) turnover in mouse resident peritoneal macrophages. The pro-oxidative effect of this diet was also studied. Female C57BL/6 mice were weaned at 21 days of age and assigned to either the experimental diet containing coconut oil (COCO diet), or the control diet containing soybean oil as fat source (10 mice per group). The fat content of each diet was 15% (w/w). Mice were fed for 6 weeks and then sacrificed. The concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…In animal studies, saturated fat feeding caused symptoms of oxidative stress [Oliveros et al, 2004;Diniz et al, 2004], while in humans, reduction of the saturated fat intake was associated with a diminished LDL susceptibility to oxidation [Yu-Poth et al, 2000], and a saturated fat replacement for the monounsaturated or polyunsaturated fat lowered plasma cholesterol, LDL-cholesterol and HDL--cholesterol [Hodson et al, 2001].…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, saturated fat feeding caused symptoms of oxidative stress [Oliveros et al, 2004;Diniz et al, 2004], while in humans, reduction of the saturated fat intake was associated with a diminished LDL susceptibility to oxidation [Yu-Poth et al, 2000], and a saturated fat replacement for the monounsaturated or polyunsaturated fat lowered plasma cholesterol, LDL-cholesterol and HDL--cholesterol [Hodson et al, 2001].…”
Section: Resultsmentioning
confidence: 99%
“…If so, this action must occur through an antioxidant mechanism that is independent of ␣ -tocopherol. Another explanation is that a low cellular PUFA content, such as occurs when the medium is not supplemented with high concentrations of PUFA, results in increased oxidative stress as reported following the feeding of a low PUFA diet to mice [44] . A third explanation is that PUFA may prevent the efficient assembly of NADPH oxidase because of changes in membrane composition, fluidity or organization.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of saturated and unsaturated fats induce oxidative stress in rat liver (MARCZUK-KRYNICKA et al, 2009), as found by Oliveros et al (2004), when increasing the levels of TBARS tissues of rats fed a diet rich in saturated fat. In the present study, it was observed an increase in the levels of MDA (also determined by TBARS) in the liver of rats fed a diet rich in fat pork.…”
Section: Discussionmentioning
confidence: 91%